1989
DOI: 10.3168/jds.s0022-0302(89)79359-0
|View full text |Cite
|
Sign up to set email alerts
|

Milk Production in Lactating Buffalo Receiving Recombinantly Produced Bovine Somatotropin

Abstract: Thirty healthy Murrah buffalo (Bubalus bubalis) in their second to fourth lactations were selected from the herd at the National Dairy Research Institute, Karnal, Haryana, India, for use in a 35-d study to determine the effects of recombinantly produced bovine somatotropin on milk production, milk composition, and dry matter intake. Treatments were daily injections of 0, 25, or 50 mg somatotropin per animal for 14 d. All buffalo consumed green chopped fodder ad libitum plus a predetermined quantity of concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
1
5

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 6 publications
5
16
1
5
Order By: Relevance
“….Administration of rBST in doses of 25 and 50 mg/day i.m. for 14 days increase milk production without affecting fat and protein (Ludri et al, 1989) contrary to increased fat, protein and lactose observed in this study. The reasons of such short term treatment on milk composition of buffaloes require further investigation as milk composition is influenced by energy balance and mobilization of body reserves (Eppard et al, 1985;Peel et al, 1982 andTyrrell et.…”
Section: Discussioncontrasting
confidence: 95%
“….Administration of rBST in doses of 25 and 50 mg/day i.m. for 14 days increase milk production without affecting fat and protein (Ludri et al, 1989) contrary to increased fat, protein and lactose observed in this study. The reasons of such short term treatment on milk composition of buffaloes require further investigation as milk composition is influenced by energy balance and mobilization of body reserves (Eppard et al, 1985;Peel et al, 1982 andTyrrell et.…”
Section: Discussioncontrasting
confidence: 95%
“…Further, IGF-I role as an independent hormone in milk secretion in absence of PRL (inhibition) was not found, although both GH and IGF-I acts synergistically with PRL hormone. The role of GH as a galactopoietic hormone is well established in buffaloes (Ludri et al, 1989;Singh and Ludri, 1994), however, this study confirm that GH and PRL are required for normal milk secretion in buffaloes. Further studies are required to be carried out to explore the mode of action of GH on mammary gland in absence of plasma PRL.…”
Section: Discussionsupporting
confidence: 53%
“…Com relação às pesquisas sobre o uso da somatotropina recombinante bovina em outras espécies ruminantes foi relatado que a rBST é biologicamente ativo em ovinos (BAUMAN, 1992), em caprinos (KNIGHT et al, 1990;PROSSER et al, 1991;DISENHAUS et al,1995) e em búfalas (LUDRI et al, 1989;POLIDORI et al, 1997, SRINIVASA-RAO & RANGANADHAM, 2000JORGE et al, 2002).…”
Section: Lista De Tabelasunclassified
“…Com relação aos outros constituintes do leite como contagem de células somáticas, teor de lactose do leite e sólidos totais, os trabalhos estão em consenso quando afirmam não haver influência do tratamento sobre nenhum dos constituintes do leite, bem como seu uso na fabricação de queijos e derivados lácteos não sofre qualquer alteração (FERRARA et al, 1989;LUDRI et al, 1989;BALDI, 1999;JORGE et al, 2002;ABO EL-NOR et al, 2007).…”
Section: Considerações Sobre a Somatotropinaunclassified